RANCANGAN TOOLSTORE PADA FASILITAS OVERHAUL DAN PERBAIKAN KOMPONEN PESAWAT TERBANG DI PT. XYZ - Lilies Esthi Riyanti; Fiqri Raka Fadillah; Djoko Herwanto (Jurnal Penelitian, 2023)
In carrying out its functions, an Approved Maintenance Organization (AMO) requires tools that are used to support and assist technicians in carrying out aircraft maintenance and components on the aircraft by existing procedures. At PT. XYZ as AMO, the room has not been separated between the tools storage room and the work area. Several problems arise because the tools storage room and the work area are still unified and the standards in the existing tools storage room have not been met. The problems that occur include, there is corrosion on several tools, there are tools that are missing from the storage area because they are scattered during the use and return process, there are findings in internal quality audits in the field of maintenance, especially in the reception and handling of tools that are not optimal. From these problems, it is necessary to design a storage room for tools regarding existing standards as a form of advice for companies in making a storage room for tools. The tool store design will be made with full attention to room conditions, lighting, temperature, and humidity under CASR 145 standards and determine the layout, number of shelves, and cabinets needed to place and store general tools and special tools.